Total Synthesis of Apigenin Glycosides and the Effect of These Compounds on Polyphenol Oxidase Enzyme Activity - Beyaztas1, S.; Kucukislamoglu2, M.; Sonmez2, F.; Nebioglu2, M.; Besoluk3, S.; Arslan2, M.; Zengin2, M.; Arslan1, O. (Asian Journal of Chemistry, 2014)
We have succeeded in total synthesis of apigenin 7-O-b-D-cellobioside (1a) and apigenin 7-O-b-D-cellobiosyl-4'-O-b-D-glucopyranoside (1c) via four and six steps in a total yield of 56 and 76 % from naringenin (2), respectively. We also synthesized apigenin 7-O-b-D-glucopyranoside (1b) and apigenin 7,4'-di-O-b-D-glucopyranoside (1d) from naringenin (2). We also examined two monoglycoside and two diglycoside with polyphenol oxidase (PPO) from potato (Solanum tuberosum). The result showed that 1a inhibited the polyphenol oxidase enzyme activity. The value of IC50 was 1.08 mM. 1b was activator effect on polyphenol oxidase enzyme activity. On the other hand, apigenin 7,4'-di-O-glycosides (1c-d) showed no activator and inhibitor effect on polyphenol oxidase enzyme activity.